The Concept and Importance of STEAM Education in Higher Educational Institutions - Shokhafizova, Nodina (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article discusses the theoretical foundations, content, and practical significance of the STEAM education concept, which is gaining wide popularity in the modern higher education system. The authors analyze the role of this concept in integrated teaching of Science, Technology, Engineering, Arts, and Mathematics, its importance in guiding students to creative and critical thinking, and its effectiveness in forming professional competencies. The article also scientifically analyzes existing experiences, problems, and promising directions in the implementation of the STEAM education approach in higher education institutions of Uzbekistan.